(3aGYdjI HQfGeL hSGFW eJYOOI ai JfejI GdeaGgje GdQjGVjI ddJdGejP Phi UYhHGJ GdJYde HGdMdbI GdChdi ef GdJYdje GdCSGSi hGJLGgGJge fMh GdQjGVjGJ (B= s The effectiveness of a multimedia program in developing mathematical concepts of first stage primary pupils with learning difficulties and their attitudes toward mathematics - (3gTGe GdTMGJ MSfjf HSjhfi s; (3Ced YHOGdaJGM ShjOGf (B: s; (3eUWai YHOGdSejY eMeO (B: s ((3GdbGgQI (B: s (3gTGe GdTMGJ MSfjf HSjhfi (B: s, 2012)
(3gOaJ GdOQGSI GdMGdjI Edi HfGA HQfGeL hSGFW eJYOOI dJfejI GdeaGgje GdQjGVjI ddJdGejP Phi UYhHGJ GdJYde HGdMdbI GdChdi ef GdJYdje GdCSGSi (B( (3GdUa GdKGdK GdGHJOGFi (B) (3hJfejI GJLGgGJge fMh JYde GdQjGVjGJ hGdJYQa Ydi aGYdjI HQfGeL GdhSGFW GdeJYOOI ai YdGL UYhHGJ GdJYde dOjge (B: (3hJchfJ YjfI GdOQGSI ef eLehYJjf GdChdi JLQjHjI hGdKGfjI VGHWI bhGe cd eLehYI(B{u(306F2(B}{u(306F0(B} (3JdejPG hJdejPI (B: (3hNdUJ GdOQGSI Edi hLhO aQb OGd EMUGFjG YfO eSJhi OdGdI (B{u(306F0(B}(3,(B{u(306F0(B}{u(306F1(B}(3dUGdM GdeLehYI GdJLQjHjI GdJi OQSJ HGSJNOGe HQfGeL GdhSGFW GdeJYOOI ajeG jNU JfejI GdeaGgje hGdJMUjd GdeYQai eeG jOd Ydi aGYdjI HQfGeL GdhSGFW GdeJYOOIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ GdJQHhjI (B- (3bSe JcfhdhLjG GdJYdje hJYje GdcHGQs
(3UOQ GjVG cbQU eOeLs
Keywords: (3HQfGeL GdhSGFW GdeJYOOI s; (3JfejI GdeaGgje s; (3UYhHGJ GdJYde s